Learning-facilitated long-term depression and long-term potentiation at mossy fiber—CA3 synapses requires activation of β-adrenergic receptors - Hagena, Hardy; Manahan-Vaughan, Denise (Frontiers in Integrative Neuroscience, 2012)
Learning-facilitated plasticity refers to hippocampal synaptic plasticity that is facilitated by novel spatial learning events. Both long-term potentiation (LTP) and long-term depression (LTD) are facilitated by novel hippocampus-dependent learning. This has important ramifications for our understanding of how the hippocampus encodes memory. One structure that is rarely studied in vivo, but is believed to be crucially important for working and long-term memory processing is the hippocampal CA3 region. Whereas learning-facilitated plasticity has been described in this structure, the mechanisms underlying this phenomenon have not been explored. The noradrenergic system plays an important role in arousal and qualification of new information as salient. It regulates synaptic plasticity in the dentate gyrus and CA1, but nothing is known about the regulation by the noradrenergic system of synaptic plasticity in the CA3 region. We explored whether ß-adrenergic receptors contribute to learning-facilitated plasticity at mossy fiber-CA3 synapses of behaving rats. We found that receptor antagonism had no effect on basal synaptic transmission, short-term potentiation, short-term depression, long-term potentiation (LTP), or LTD, that were electrically-induced by patterned afferent stimulation. We found however, that both learning-facilitated LTP and LTD were prevented by antagonism of ß-adrenergic receptors, whereas the agonist isoproterenol facilitated short-term potentiation (STP) into LTP. Thus, learning-facilitated and electrically-induced plasticity may not share the same prerequisites. These results support that the mossy fiber synapse engages in a distinct aspect of encoding of spatial information that involves both LTP and LTD. Furthermore, changes in arousal that are coupled to new learning are associated with activation of hippocampal ß-adrenergic receptors that in turn comprise a key element in this type of information acquisition and processing by the CA3 region.